2019
DOI: 10.9734/ajee/2019/v9i330099
|View full text |Cite
|
Sign up to set email alerts
|

Ecological Risk Assessment of Heavy Metals in Soil of an Open Dump along Old Ikare Road Owo, Ondo State, Nigeria

Abstract: Aims: To investigate the heavy metal concentrations in soil samples collected from an open dumpsite in a rural community (Aba Idi-Mangoro) in Owo, Ondo State and to compare the observed values with the regulatory limits. This study also aimed to determine the pollution levels using tools like contamination factor, pollution load index and geoaccumulation index. Study Design: Field study design was use in this study. Place and Duration of Study: Soil samples were collected from Aba Idi-Mangoro in Ow… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
3
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 27 publications
0
3
0
Order By: Relevance
“…Some studies have reported that even at lower concentrations, Cd and Pb could be detrimental to human and animal health (Garai et al, 2021). Additionally, the net result of uptake is bioaccumulation; therefore, longterm exposure to heavy metals can cause death or impairment of vital organs such as the central nervous system, kidney and liver and could be genotoxic (Garai et al, 2021;Olayinka-Olagunju, 2021;Dou et al, 2022).…”
Section: Discussionmentioning
confidence: 99%
“…Some studies have reported that even at lower concentrations, Cd and Pb could be detrimental to human and animal health (Garai et al, 2021). Additionally, the net result of uptake is bioaccumulation; therefore, longterm exposure to heavy metals can cause death or impairment of vital organs such as the central nervous system, kidney and liver and could be genotoxic (Garai et al, 2021;Olayinka-Olagunju, 2021;Dou et al, 2022).…”
Section: Discussionmentioning
confidence: 99%
“…Metal contamination in aquatic environments has become a global issue. It is worsening at an alarming rate (Al-Afify and Abdel-Satar 2022), with consequent threats to the food chain of animals (Olayinka-olagunju 2021). Metals are non-biodegradable substances that naturally occur in the upper part of the lithosphere and are constantly deposited through anthropogenic activities and become integrated into the sediment, water, and aquatic biota, causing aquatic ecosystem contagion (Briffa et al 2020).…”
Section: Introductionmentioning
confidence: 99%
“…This agrees with the findings ofOlatunji-Ojo et al (2019) that reported high concentrations of Fe in all the three sampling rivers in Ilaje LGA, Nigeria. It is essential to know that the Nigerian soil has a very high concentration of Fe and this may be due to the chemical composition of the country's parent soils(Olayinka-Olagunju et al 2019;…”
mentioning
confidence: 99%